Glass surfaces : proceedings of the fourth Rolla Ceramic Materials Conference on Glass Surfaces, St. Louis, Missouri, USA, 15-19 June, 1975 - Day, D. E. (North-Holland Pub. Co. ; American Elsevier, 1975)
Glass Surfaces covers the proceedings of the Fourth Rolla Ceramic Materials Conference on Glass Surfaces. The book presents 38 papers that are organized according to their respective theme. The text first covers the structure of subsurface layers and their role in glass technology, and then proceeds to discussing surface characterization and experimental techniques. Next, the book talks about interfacial phenomena, such as interdiffusion of hydrogen and alkali ions in a glass surface and interdiffusion of hydrogen and alkali ions in a glass surface. The fourth part covers corrosion and chemica.